The impact of pulsed electric fields on milk’s macroand micronutrient profile: a comprehensive review - Mohamad, Azizah; Abdul Karim Shah, Nor Nadiah; Sulaiman, Alifdalino; Mohd Adzahan, Noranizan; Arshad, Rai Naveed; Muhammad Aadil, Rana (Multidisciplinary Digital Publishing Institute, 2023)
Consumers around the world are attracted to products with beneficial effects on health. The stability, functionality, and integrity of milk constituents are crucial determinants of product quality in the dairy industry. Milk contains macronutrients and micronutrients that aid in a wide range of physiological functions in the human body. Deficiencies of these two types of nutrients can confine growth in children and increase the risk of several diseases in adults. The influence of pulsed electric fields (PEF) on milk has been extensively reviewed, mostly concentrating on the inactivation of microbes and enzymes for preservation purposes. Therefore, the information on the variations of milk macro- and micronutrients treated by PEF has yet to be elucidated and it is imperative as it may affect the functionality, stability, and integrity of the milk and dairy products. In this review, we describe in detail the introduction, types, and components of PEF, the inactivation mechanism of biological cells by PEF, as well as the effects of PEF on macro- and micronutrients in milk. In addition, we also cover the limitations that hinder the commercialization and integration of PEF in the food industry and the future outlook for PEF. The present review consolidates the latest research findings investigating the impact of PEF on the nutritional composition of milk. The assimilation of this valuable information aims to empower both industry professionals and consumers, facilitating a thorough understanding and meticulous assessment of the prospective adoption of PEF as an alternative technique for milk pasteurization.